Impact of the non-axisymmetric SOL current driven by a biased electrode on the diverted J-TEXT plasma. (1st July 2022) - Li, Shuhao; Wang, Nengchao; Ding, Yonghua; Liang, Yunfeng; Yang, Qinghu; Mao, Feiyue; Xu, Xin; Ren, Zhengkang; Zhao, Chuanxu; Huang, Zhuo; Alhaji Bala, Abba; Chen, Zhipeng; et al.
Abstract: It is observed in EAST that the non-axisymmetric helical currents induced by lower hybrid waves (LHWs) in the scrape-off layer (SOL) can produce resonant magnetic perturbations (RMPs), hence mitigate edge-localized modes (ELMs) significantly and cause the strike points splitting. In this work, the non-axisymmetric SOL current driven by an alternative method, i.e. biased electrode, is shown to influence the plasma boundary, especially the strike points, in the divertor configuration on J-TEXT. With positive bias to the electrode, the upper strike points on the divertor target plate is observed to split as captured by the visible camera. Such splitting is usually observed with the RMPs. In addition, the SOL plasma parameters measured by the reciprocating probe, such as floating potential ( V f ), electron temperature ( T e ), and ion saturation current ( I s ), are significantly altered by applying modulation bias, which is closely related to the SOL current. A SOL current model has been extended from the limiter configuration version to the poloidal divertor configuration, and the magnetic field generated by SOL current and the change of magnetic topological structure of plasma boundary can be simulated. The simulation results shows that the magnetic perturbation generated by the SOL current can induce the lobes near the X-point, which is three-dimensional asymmetric structure, and shows good agreement with the experimental observation. The active control of the boundary magnetic topology indicates that the SOL current is capable of generating strong magnetic perturbations, and hence might be sufficient for the control of ELMs.